Give me poetical science: an invited speaker abstract for RM4ACI (Research Methods in ACI) workshop - North, Steve (2016)
My big themes in this paper are: (i) ‘poetical science’: amalgamating quantitative and qualitative methods into a new hybrid approach for ACI and (ii) identifying ‘honest’ routes to user-centred design for ‘unaware’ interactors (be they neurodiverse humans or nonhuman animals).